Testbeds and research infrastructures for the development of networks and communities : 11th International Conference, TRIDENTCOM 2016, Hangzhou, China, June 14-15, 2016, Revised selected papers /: 11th International Conference, TRIDENTCOM 2016, Hangzhou, China, June 14-15, 2016, Revised selected papers. ([2017]) - Unknown
No abstract available